Overexpression of luxS Cannot Increase Autoinducer-2 Production, Only Affect the Growth and Biofilm Formation in Streptococcus suis. (7th November 2013) - Wang, Yang; Yi, Li; Zhang, Zhicheng; Fan, Hongjie; Cheng, Xiangchao; Lu, Chengping
Abstract : LuxS/AI-2 quorum sensing (QS) system involves the production of cell signaling molecules via luxS -based autoinducer-2 (AI-2). LuxS has been reported to plays critical roles in regulating various behaviors of bacteria. AI-2 is a byproduct of the catabolism of S-adenosylhomocysteine (SAH) performed by the LuxS and Pfs enzymes. In our previous study, the function of LuxS in AI-2 production was verified in Streptococcus suis (SS). Decreased levels of SS biofilm formation and host-cell adherence as well as an inability to produce AI-2 were observed in bacteria having a luxS mutant gene. In this study, the level of AI-2 activity exhibits a growth-phase dependence with a maximum in late exponential culture in SS. An SS strain that overexpressed luxS was constructed to comprehensively understand the function of AI-2. Overexpressed luxS was not able to increase the level of pfs expression and produce additional AI-2, and the bacteria were slower growing and produced only slightly more biofilm than the wild type. Thus, AI-2 production is not correlated with luxS transcription. luxS expression is constitutive, but the transcription of pfs is perhaps correlated with AI-2 production in SS.